PENGENALAN HURUF HIJAIYAH SISWA KELAS 3 SD DENGAN METODE IQRO’ DAN TILAWATI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DI TPQ AL-ITTIHAD-KEDIRI: Studi Pengabdian Pada Masyarakat - Umi Hanik; Sania Amirah Husna (Abdimas Indonesian Journal, 2021)
Abstract. The Qur'an is a holy book that is used as a guide and source of Islamic law. The Qur'an itself is delivered in Arabic which is maintained in its purity. In Indonesia, the mother tongue of the people is Indonesian. In addition, cultural and social diversity makes people communicate daily in local languages. This fact makes Arabic even more backward because it is not the first language in its use. There are many ways to deepen the knowledge of reading the Qur'an. One of them is the Tilawati and Iqro 'method. In the service of KKN in Wonorejo village, the author found problems in grade 3 elementary school students with the initials D who were 9 years old. The point of the problem found is that the research subjects are less able to read hijaiyah letters in succession smoothly. In addition, the subject does not want the material to be repeated from volume 3 on the basis that it has reached volume 6 in the previous TPQ. This study uses a combination of two different methods at the same time because it adapts to the learning needs of the research subject. The research method used is single subject research (SSR) with an A-B design where A is the baseline phase and B is the intervention (treatment) phase. The study was conducted in 14 sessions (5 baseline sessions and 9 intervention sessions) within 10 minutes of each session. The results show a 40% increase in the rate of change. In other words, the application of the combination method of iqro 'with tilawati can improve the ability to read the Qur'an in grade 3 elementary school students at TPQAl-Ittihad.